Editorial - Gómez Botero, Maryory Astrid; Isaza Ramírez, Sebastián (Revista Facultad de Ingeniería Universidad de Antioquia, 2019)
The world’s population in creases every year and resources are limited, consequently the humanity faces the need to reinvent the way of living. As population grows, it is expected that in the coming years, the majority of people will live in urban areas.